The role of NUDT21 in microRNA‐binging sites of EZH2 gene increases the of risk preeclampsia. Issue 5 (18th March 2019) - Lang, Xiao; Zhao, Wenxia; Huang, Ding; Liu, Wei; Shen, Hong; Xu, Liang; Xu, Shan; Huang, Yongfang; Cheng, Weiwei
Abstract: Objectives: Preeclampsia (PE) is a major cause of mortality and morbidity among pregnant mothers and their fetuses worldwide. Recent studies have shown that several microRNAs (miRNAs) play crucial role in pathogenesis of PE patients; however, the mechanisms responsible for differences in miRNA function in PE largely remain to be determined. Materials and Methods: We studied that NUDT21 expression was markedly increased, whereas EZH2 was decreased in placental samples from patients with PE. We identified NUDT21 as an interaction partner of enhancer of zeste homologue 2 (EZH2). NUDT21 co‐localized with EZH2 in the human trophoblast cell line, HTR‐8/SVneo and NUDT21 was shown to bind to EZH2 in RNA immunoprecipitation assays. NUDT21 has previously been reported to be involved in alternative polyadenylation; thus, the interaction between NUDT21 and EZH2 may play an important role in the crosstalk between alternative polyadenylation (APA) and miRNA‐mediated gene silencing in PE. Results: In the human trophoblast cell line HTR‐8/SVneo, loss‐of‐function assays indicated that knockdown of NUDT21 suppressed cell proliferation, migration and tube formation. Furthermore, functional studies showed that NUDT21 elongated the 3'‐UTR of mRNAs thereby exposing more miRNA binding sites (including miR138 and miR363), which enhanced the efficiency of miRNA‐mediated gene silencing and promoted EZH2 binding. Conclusions: This is the first report about the relationship of NUDT21 and EZH2. The data indicate that the aberrant expression of NUDT21 contributes to PE by targeting 3'‐UTR of EZH2 mRNA. These findings may provide novel targets for future investigations into therapeutic strategies for PE.